An analytically derived delineation of the West African Coastal Province based on bivalves - (:unkn) unknown (My University, 2022)
Aim To assess the pattern of biotic regions (BR) and their boundaries, to detect chorotypes and to relate these patterns to key environmental factors. Location Eastern Atlantic Ocean. Time period Recent. Taxon studied Bivalvia. Methods Distributions were scored for 595 species. Operational geographical units are classified hierarchically using Baroni-Urbani & Buser similarity index, clusters were assessed for statistical significance with the ‘RMacoqui 1.0’ software using G tests of independence, and chorotypes were inferred likewise from similarity between species distributions. Results Three strong biotic boundaries delimit four BR: (1) European Atlantic and Mediterranean; (2) West African, from western Sahara to southern Angola; (3) Baia dos Tigres/Namibia; and (4) Saint Helena/Ascension. The West African BR is subdivided by two weak boundaries into three subordinate BR: the tropical region proper, the north-western African transition zone and the cluster (southern Angola/São Tomé/Cape Verde Islands). Of the 429 species present in West Africa, 261 (60.7%) are endemic, and 19&nbsp
Keywords: African Research